2016
DOI: 10.1016/j.msea.2016.09.100
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic recrystallization mechanisms and twining evolution during hot deformation of Inconel 718

Abstract: The hot deformation behavior of an IN718 superalloy was studied by isothermal compression tests under the deformation temperature range of 950–1100 °C and strain rate range of 0.001–1 s-1 up to true strains of 0.05, 0.2, 0.4 and 0.7. Electron backscattered diffraction (EBSD) technique was employed to investigate systematically the effects of strain, strain rate and deformation temperature on the subgrain structures, local and cumulative misorientations and twinning phenomena. The results showed that the occurr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
61
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 211 publications
(65 citation statements)
references
References 74 publications
2
61
0
Order By: Relevance
“…(17), (18) and (19), it can be found that the influences of initial δ phase on DRX are comprehensively considered in Eq. (17). Therefore, the new developed DRX kinetic model shows the distinct advantages for predicting the DRX behavior of the studied superalloy at complicated aging conditions.…”
Section: Comparisons Of Different Drx Kinetics Modelsmentioning
confidence: 98%
See 2 more Smart Citations
“…(17), (18) and (19), it can be found that the influences of initial δ phase on DRX are comprehensively considered in Eq. (17). Therefore, the new developed DRX kinetic model shows the distinct advantages for predicting the DRX behavior of the studied superalloy at complicated aging conditions.…”
Section: Comparisons Of Different Drx Kinetics Modelsmentioning
confidence: 98%
“…In recent years, numerous researches have been executed to study the high-temperature deformation behaviors [11,12], hot tensile fracture characteristics [13,14], microstructural evolution [15,16,17], and hot workability [18,19] of some typical superalloys. Lin et al [20,21,22] developed accurate phenomenological and physical-base constitutive models to predict high-temperature deformation behavior for GH4169 superalloy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dynamic and post-dynamic recrystallization is among the most important phenomena impacting the microstructure of hot-forged components. The influence of the thermomechanical forging conditions on dynamic recrystallization (DRX) kinetics and on the DRX grain size is relatively well established [1][2][3][4][5][6][7][8], and can even be predicted using either physical or empirical models [9][10][11][12][13][14][15]. However, previous studies have shown that post-dynamic evolutions may also considerably impact the final microstructure [12,[15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…These severe working environments require a proper forging of the disc to be performed. Grain size control in the forging of the Inconel 718 superalloy is a very important issue because the grain size is closely related to the mechanical properties and the performance of the discs [1] [2]. Na et al [3] studied the evolution of the microstructure in the process of two-step blade forging of 718 alloy using a 3D FE simulator that contained a microstructure module.…”
Section: Introductionmentioning
confidence: 99%